The Effectiveness of Lecture Methods in Learning Fiqh Using Practice Methods at SMP Ar Rahman Medan - Gita Gania Godelova; Weni Aulia Harahap (Yayasan Rahmat Islamiyah, 2023)
This research was conducted to determine the effectiveness of teaching fiqh using lecture and practice methods at Ar Rahman Middle School. Even this research was carried out only within the scope of certain classes, namely class VII, VIII, and IX. The researcher also wanted to know which method had more influence on the learning outcomes of SMP Ar Rahman students and which method was preferred by the students. The researcher used a quantitative research using a survey method. The quantitative method is a type of scientific research based on the philosophy of positivism. The data collection techniques used were interviews and observations. The results of our research show that the implementation of fiqh lessons for grades VII, VIII, and IX is carried out in one place and delivered by the same teacher, and is carried out in one place as well as one time. meeting in a week i.e. on Friday only. We see that the practical method has a greater influence on this learning compared to the lecture method. It is very important to learn fiqh from a young age in order to better understand the scientific disciplines that study and describe the basic legal norms regarding Islam and according to the Sunnah of the Prophet. Of course the hope of achieving this learning is that students can practice it in everyday life and it is hoped that it will continue to be embedded in students.